2021
DOI: 10.1002/oby.23096
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Adiposity Elevates the Risk of Critical Condition in COVID‐19: A Systematic Review and Meta‐Analysis

Abstract: Objective A higher body mass index (BMI) has become acknowledged as one of the important risk factors for developing critical condition in coronavirus disease 2019 (COVID‐19). In addition to BMI, body composition, particularly visceral adiposity, might be an even more accurate measure to stratify patients. Therefore, we aimed to evaluate the association between the distributions of CT‐quantified fat mass and critical condition of patients with COVID‐19. Methods A system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 35 publications
(50 reference statements)
1
56
0
2
Order By: Relevance
“…Table 1 depicts the list of main studies and meta-analyses associating obesity or BMI or visceral fat with COVID-19 risk and outcomes including the severity of infection, hospitalizations, hospitalizations in the ICU, administration of invasive mechanical ventilation (IMV), and mortality [19][20][21][22][23]24••, 25-30, 31••, [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Current Evidence Of Epidemiologic Associations Between Obesity and Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 depicts the list of main studies and meta-analyses associating obesity or BMI or visceral fat with COVID-19 risk and outcomes including the severity of infection, hospitalizations, hospitalizations in the ICU, administration of invasive mechanical ventilation (IMV), and mortality [19][20][21][22][23]24••, 25-30, 31••, [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Current Evidence Of Epidemiologic Associations Between Obesity and Covid-19mentioning
confidence: 99%
“…In a prospective observational cohort study analyzing 166 patients with respiratory symptoms who presented at an emergency department in the Netherlands, increased WHR was an independent risk factor for respiratory distress in COVID-19 (OR 1.11, 95% CI: 1.02-1.20), adjusting for age, gender, BMI, and metabolic syndrome. Based on recent meta-analyses of retrospective studies, an abnormal fat distribution, particularly visceral adipose tissue (VAT) expansion determined by computed tomography (CT)-based quantification, was found to be a significant independent factor of hospitalization, admission to the ICU, and worse clinical outcomes such as the need of intubation, adjusting for age, gender, and BMI [46,47]. Difficult airway management and prone positioning (critical in the [58][59][60].…”
Section: Current Evidence Of Epidemiologic Associations Between Obesity and Covid-19mentioning
confidence: 99%
“…Recent publications have reported that higher BMI, higher abdominal visceral adipose tissue, higher intermuscular adipose tissue, reduced liver density, reduced lumbar SMD, and reduced pectoral muscle area are associated with worse clinical outcomes in COVID-19 patients in terms of disease severity and death [ 5 , 19 25 ]. While CT scans of the abdomen are rarely available for unselected series of COVID-19 patients, chest CT has been widely used in some centers to rapidly assess the presence of pneumonia and stratify patients with different disease severity [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The possible role of body composition parameters as prognostic factors for COVID-19 severity has been initially explored [ 5 , 19 , 20 , 22 25 ]. However, the underlying causal relationship remains to be determined and contextualized in the complex pathogenetic pathways involved in COVID-19 progression.…”
Section: Introductionmentioning
confidence: 99%
“…Those adipocytes may be directly infected by SARS-CoV-2, leading to aggravation of the inflammatory infiltrate and massive interstitial edema. A meta-analysis that pooled three studies with 208 patients showed that patients who needed invasive mechanical ventilation (IMV) had higher visceral fat area values than patients who did not need IMV (37), indicating the risk of respiratory dysfunction in patients with obesity and severe COVID-19.…”
Section: Obesity and Covid-19mentioning
confidence: 99%